SPLITSVILLE: A Play-with-Music Exploring Improper Divorce Disclosure’s Effects on Children - Emily Abigail (Kata Kita: Journal of Language, Literature, and Teaching, 2021)
Going through a divorce is a difficult time for a family, including the children. In this COVID-19 pandemic era, when the divorce rate in Indonesia soars high, I conducted a research to find out how it affects children or how children respond to it, especially when the decision to divorce is taken without their knowledge. To analyze it, I used theories from communication science. From the result of that research, I made a musical script which portrays my findings, in the hopes that readers or audiences can understand children’s perspective of divorce. The findings are the fact that it makes children become aloof and lowers their self-esteem. Even though they have a lot of questions and uncertainties towards the future, they will choose to become distant to avoid the topic of divorce. The reasons being they are afraid that talking about it will bring more drastic change. Other than that, they do not trust their parents as much anymore, since they think that the parents have lied to them.Keywords: divorce, children, communication, aloof, play-with-music, comedy